RABBITFISH GROWTH PATTERNS IN THE WATERS OF THE ALAS STRAIT, WEST NUSA TENGGARA PROVINCE (ALBACORE Jurnal Penelitian Perikanan Laut, 2025)
Baronang fish is a type of fish that is commonly found in the waters of the Alas Strait. Baronang fishing carried out continuously can affect the growth and existence of baronang fish in waters. This study aims to find out the types of baronang fish, the composition of types and sizes of baronang fish, as well as to find out the growth pattern of baronang fish caught in the waters of the Alas Strait. This research was conducted from April to June 2025. Data collection was carried out through interviews who were selected using the Snowball sampling method and direct measurements. Fish length measurement was carried out with the WCS Image Tools application, and the data obtained was analyzed through identification, length distribution analysis, type composition, and the relationship between length and weight of baronang fish. The results of the study show that there are 7 species of baronang fish in the waters of the Alas Strait. The species Siganus canaliculatus is the most common species found in the waters of the Alas Strait, with a percentage of 53.15%. On the other hand, the species with the lowest number of individuals are Siganus corallinus and Siganus spinus, which is equivalent to a percentage of 0.23%. The growth pattern of baronang fish in the waters of the Alas Strait showed a negative allometric growth pattern (b